2016
DOI: 10.4172/pharmaceutical-sciences.1000150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Contents and Antimicrobial Activities of Commercial and Natural Cinnamon Oils

Abstract: There has been an increased interest in essential oils in recent years in accordance with new treatments against pathogens. The aim of the present study was to investigate the contents and to compare the antimicrobial activity of different brands of commercial oils with two natural cinnamon oils. Antibacterial and antifungal activities of cinnamon oils were estimated using disc diffusion and macro dilution methods against Enterococcus faecalis ATCC 19433, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…This variation in the results may be due to different manufacturing processes of the standard. 5,13 In this study it was observed that the mean zone of inhibition of onion extract against Pseudomonas aeruginosa was 5.06 mm±0.24, similarly in a study conducted by N Azu et al, found that the zone of inhibition of onion extract against Pseudomonas aeruginosa was 17mm. 14 In the current study the mean zone of inhibition of quercetin against Pseudomonas aeruginosa was found to be 14.30 mm±1.96 , Jaisinghani et al, conducted similar study and found the antimicrobial effect of quercetin against Pseudomonas aeruginosa through different parameters.…”
Section: Discussionsupporting
confidence: 68%
“…This variation in the results may be due to different manufacturing processes of the standard. 5,13 In this study it was observed that the mean zone of inhibition of onion extract against Pseudomonas aeruginosa was 5.06 mm±0.24, similarly in a study conducted by N Azu et al, found that the zone of inhibition of onion extract against Pseudomonas aeruginosa was 17mm. 14 In the current study the mean zone of inhibition of quercetin against Pseudomonas aeruginosa was found to be 14.30 mm±1.96 , Jaisinghani et al, conducted similar study and found the antimicrobial effect of quercetin against Pseudomonas aeruginosa through different parameters.…”
Section: Discussionsupporting
confidence: 68%
“…; Kaskatepe et al . ). For instance, a previous study demonstrated a significant difference in MIC values against a broad range of micro‐organisms when five cinnamon oils with different brands and different chemical contents were tested (Kaskatepe et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, the composition of essential oil is documented to vary according to environmental and climatic conditions (Hammer et al 1999). The different chemical constituents in essential oils have been reported to exhibit different antimicrobial activities (Li et al 2013;Kaskatepe et al 2016). For instance, a previous study demonstrated a significant difference in MIC values against a broad range of micro-organisms when five cinnamon oils with different brands and different chemical contents were tested (Kaskatepe et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among polyphenols, CEO contains mainly vanillic, caffeic, p-Coumaric, safrol and ferulic acid (Muchuweti et al, 2007). Cinnamaldehyde is the most reported volatile substance in CEO, with a content ranging from 50 to 90% (Gupta et al, 2008;Wong et al, 2014;Kaskatepe et al, 2016 ). CEO used in the present study comprised 54.35% of cinnamaldehyde together with eugenol (16.59%), beta-Caryophyllene (6.93%) and linalool (6.37%) ( Table 1).…”
Section: Resultsmentioning
confidence: 87%